Development of Formaldehyde Adsorption using Modified Activated Carbon â€“ A Review - Rengga, W.D.P; Sudibandriyo, M.; Nasikin, M (International Journal of Renewable Energy Development, 2012)
Gas storage is a technology developed with an adsorptive storage method, in which gases are stored as adsorbed components on the certain adsorbent. Formaldehyde is one of the major indoor gaseous pollutants. Depending on its concentration, formaldehyde may cause minor disorder symptoms to a serious injury. Some of the successful applications of technology for the removal of formaldehyde have been reported. However, this paper presents an overview of several studies on the elimination of formaldehyde that has been done by adsorption method because of its simplicity. The adsorption method does not require high energy and the adsorbent used can be obtained from inexpensive materials. Most researchers used activated carbon as an adsorbent for removal of formaldehyde because of its high adsorption capacity. Activated carbons can be produced from many materials such as coals, woods, or agricultural waste. Some of them were prepared by specific activation methods to improve the surface area. Some researchers also used modified activated carbon by adding specific additive to improve its performance in attracting formaldehyde molecules. Proposed modification methods on activation and additive impregnated carbon are thus discussed in this paper for future development and improvement of formaldehyde adsorption on activated carbon. Specifically, a waste agricultural product is chosen for activated carbon raw material because it is renewable and gives an added value to the materials. The study indicates that the performance of the adsorption of formaldehyde might be improved by using modified activated carbon. Bamboo seems to be the most appropriate raw materials to produce activated carbon combined with applying chemical activation method and addition of metal oxidative catalysts such as Cu or Ag in nano size particles. Bamboo activated carbon can be developed in addition to the capture of formaldehyde as well as the storage of adsorptive hydrogen gas that supports renewable energy.Â Keywords: adsorption; bamboo; formaldehyde; modified activated carbon; nano size particles